Provenance and dispersal patterns of sediments on the continental shelf of northern South China Sea: Evidence from detrital zircon geochronology - Jia, Junmin; Wang, Ce; Su, Ming; Yan, Wen; Zeng, Letian; Cui, Heqi (Marine geology, 2023)
The northern shelf of South China Sea is an important passageway for the transportation of sediments from the terrigenous source to the oceanic sink, but the provenance and dispersal patterns of sediments remain largely unclear. Here we report the results of zircon grain-size analysis and U-Pb geochronology to investigate the sediment provenance and illustrate the transport and dispersal patterns of sediments on the continental shelf of the northern South China Sea. The results show that detrital zircon U-Pb ages within sediments are characterized by a major peak at ca. 150 Ma, as well as three minor age populations at ca. 240 Ma, 400–500 Ma, and 900–1000 Ma. A detailed provenance study suggests that these sediments were primarily derived from both the Pearl River catchment and the drainage systems in Taiwan Island. Our study confirms that the transportation and dispersion of sediments were largely controlled by both topography and hydrodynamics of sea. The sediments in the inner continental shelf were transported from the Pearl River drainage system and subject to the Guangdong Coastal Current, whereas the sediments in the middle and outer continental shelf were markedly influenced by the South China Sea warm current. This study elucidates the transport and dispersal patterns of detrital sediments in the marginal sea by comprehensive analyses of detrital zircon grains. •Zircon grain-size and U-Pb dating were utilized to decipher the provenance and dispersal patterns.•The sediments were primarily derived from the sources of Pearl River and Taiwan Island.•Redistribution of sediments was influenced by the shelf current as the rising of sea level.•Different mineral grain sizes settling differentially can affect sediment provenance.